2020
DOI: 10.3390/antiox9111044
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antioxidants on Photoreactivity and Phototoxic Potential of RPE Melanolipofuscin Granules from Human Donors of Different Age

Abstract: One of the most prominent age-related changes of retinal pigment epithelium (RPE) is the accumulation of melanolipofuscin granules, which could contribute to oxidative stress in the retina. The purpose of this study was to determine the ability of melanolipofuscin granules from younger and older donors to photogenerate reactive oxygen species, and to examine if natural antioxidants could modify the phototoxic potential of this age pigment. Electron paramagnetic resonance (EPR) oximetry, EPR-spin trapping, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…These findings underline the importance of co-localisation of antioxidants with potential sources of reactive oxygen species. Some previous studies also indicate that zeaxanthin and/or lutein can exert protection in cultured ARPE-19 cells against photooxidative damage, and that protection is more efficient if carotenoids are co-localized with photosensitizers [92][93][94][95]. Wrona et al have shown that zeaxanthin supplemented to ARPE-19 cells exposed to visible light and merocyanine 540, a well-characterized photosensitizer which associates with cell membranes, can substantially diminish oxidation of cholesterol but does not offer a significant protection against cytotoxicity unless it is given in combination with vitamin C or vitamin E and the exposure to photooxidation is short [92].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These findings underline the importance of co-localisation of antioxidants with potential sources of reactive oxygen species. Some previous studies also indicate that zeaxanthin and/or lutein can exert protection in cultured ARPE-19 cells against photooxidative damage, and that protection is more efficient if carotenoids are co-localized with photosensitizers [92][93][94][95]. Wrona et al have shown that zeaxanthin supplemented to ARPE-19 cells exposed to visible light and merocyanine 540, a well-characterized photosensitizer which associates with cell membranes, can substantially diminish oxidation of cholesterol but does not offer a significant protection against cytotoxicity unless it is given in combination with vitamin C or vitamin E and the exposure to photooxidation is short [92].…”
Section: Discussionmentioning
confidence: 92%
“…In those studies zeaxanthin was administered to ARPE-19 cells 24 hours prior to exposure to the photosensitizer and light. In other studies, where the photosensitizers were present inside the cells, such as phagocytosed lipofuscin, melanolipofuscin, or melanosomes, a combination of zeaxanthin with vitamin E were, at least in part, preserving cell viability [93][94][95]. In these experiments, pigment granules were enriched with antioxidants prior to administration to cultured cells.…”
Section: Discussionmentioning
confidence: 93%
“…These findings underline the importance of co-localization of antioxidants with potential sources of reactive oxygen species. Some previous studies also indicate that zeaxanthin and/or lutein can exert protection in cultured ARPE-19 cells against photo-oxidative damage, and that protection is more efficient if carotenoids are co-localized with photosensitizers [ 47 , 115 , 116 , 117 ]. Wrona et al have shown that zeaxanthin supplemented by ARPE-19 cells exposed to visible light and merocyanine 540, a well-characterized photosensitizer which associates with cell membranes, can substantially diminish oxidation of cholesterol but does not offer a significant protection against cytotoxicity unless it is given in combination with vitamin C or vitamin E and the exposure to photo-oxidation is short [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In those studies, zeaxanthin was administered to ARPE-19 cells 24 h prior to exposure to the photosensitizer and light. In other studies, where the photosensitizers were present inside the cells, such as phagocytosed lipofuscin, melanolipofuscin, or melanosomes, a combination of zeaxanthin with vitamin E were, at least partly, preserving cell viability [ 115 , 116 , 117 ]. In these experiments, pigment granules were enriched with antioxidants prior to administering to cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…EPR spin trapping of photogenerated radicals were performed using 100 mM DMPO (5,5-Dimethyl-1-Pyrroline N -oxide) (Sigma-Aldrich, Saint Louis, MO, USA) as a spin trap, according to the procedure described elsewhere [ 45 ]. In brief, samples containing 0.061 mg/ml melanin in 70% DMSO (Sigma-Aldrich, Saint Louis, MO, USA) were irradiated employing the same light source as described for oxygen photoconsumption.…”
Section: Methodsmentioning
confidence: 99%